Business web strategy design, alignment and application - Al-Hakim, Latif, 1946-; Memmola, Massimo (Information Science Reference, 2009)
"This book addresses the gap in business Web strategy through a collection of concentrated managerial issues, gathering the latest theoretical frameworks, case studies, and research pertaining to maximizing the power of the Web"--Provided by publisher.